The importance of IRS monitoring to debt pricing in private firms☆ - GUEDHAMI, O; PITTMAN, J (Journal of Financial Economics, 2008)
We examine the link between Internal Revenue Service (IRS) monitoring and yield spreads on private firms’ 144A bond issues. After controlling for security-specific and other firm-specific determinants, we provide evidence that debt financing is cheaper when the probability of a face-to-face IRS audit is higher. Consistent with another prediction, we find that IRS oversight has a stronger impact on bond pricing for private firms with high ownership concentration, which suffer worse agency problems between controlling shareholders and outside investors. Collectively, our research implies that IRS monitoring plays a valuable corporate governance role by reducing information asymmetry evident in borrowing costs.